Comprehensive screening of low nitrogen tolerant maize based on multiple traits at the seedling stage - Jianjia Miao; Fei Shi; Wei Li; Ming Zhong; Cong Li; Shuisen Chen (PeerJ, 2022)
Background Plants tolerant to low nitrogen are a quantitative trait affected by many factors, and the different parameters were used for stress-tolerant plant screening in different investigations. But there is no agreement on the use of these indicators. Therefore, a method that can integrate different parameters to evaluate stress tolerance is urgently needed. Methods Six maize genotypes were subject to low nitrogen stress for twenty days. Then seventeen traits of the six maize genotypes related to nitrogen were investigated. Nitrogen tolerance coefficient (NTC) was calculated as low nitrogen traits to high nitrogen traits. Then principal component analysis was conducted based on the NTC. Based on fuzzy mathematics theory, a D value (decimal comprehensive evaluation value) was introduced to evaluate maize tolerant to low nitrogen. Results Three maize (SY998, GEMS42-I and GEMS42-II) with the higher D value have better growth and higher nitrogen accumulation under low nitrogen conditions. In contrast, Ji846 with the lowest D value has the lowest nitrogen accumulation and biomass in response to nitrogen limitation. These results indicated that the D value could help to screen low nitrogen tolerant maize, given that the D value was positively correlated with low nitrogen tolerance in maize seedlings. Conclusions The present study introduced the D value to evaluate stress tolerance. The higher the D value, the greater tolerance of maize to low nitrogen stress. This method may reduce the complexity of the investigated traits and enhance the accuracy of stress-tolerant evaluation. In addition, this method not only can screen potentially tolerant germplasm for low-nitrogen tolerance quickly, but also can comprise the correlated traits as many as possible to avoid the one-sidedness of a single parameter.